A Study on Work Life Balances in the New Normal - With Reference to Kanchipuram (International Journal of Food and Nutritional Sciences, 2022)
Balance among serious and fun activities is a goliath subject in both expert key plans and careful evaluation. The standard objective of this paper is to dispose of the issues and loads looked by specialists telecommuting during the pandemic Covid lockdown in the Indian setting as well as wreck assessments to figure out telecommuting in disturbing circumstances.